The female body as the stage of political communication on the feminist movement : A Case Study of the Corporación para la vida Mujeres que Crean - Restrepo, Paula; Sánchez, Kelly García; Giraldo, Lina Marcela; Villegas Peña, Johana (Folios, revista de la Facultad de Comunicaciones y Filología, 2014)
The research conducted on creative expressions as forms of communication of social movements, was focused on the feminist movement from the city of Medellin, where the subject of study is the body as a primary means of political communication. Through the feminist organization Corporation para la Vida Mujeres que Crean, was identified that by means of artistic techniques such as body art and performance, feminist discourse is staged in the public sphere when the body is your its canvas of protest.